2007
DOI: 10.1063/1.2472329
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio simulation of the vibrationally resolved photoelectron spectrum of Si3−

Abstract: Electron photodetachment spectra provide a wealth of information about the electronic and vibrational level structures of neutral molecules that form stable anions. Experiments carried out for the smallest polyatomic silicon cluster anion (Si3-+hupsilon-->Si3*+e-) show vibrational progressions in six observed electronic bands (X-E) of the neutral species. The authors have performed ab initio calculations using the MRCI+D/aug-cc-pVQZ level for the corresponding electronic states followed by variational calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…[14][15][16][17][18][19][20][21][22] For smaller anionic and cationic clusters, the combination of experiments with high level theory makes it possible to determine the structures of these clusters. [23][24][25] For medium-sized clusters, changes in the structural motif were suggested. Recently, we used infrared multiple photon dissociation (IR-MPD) to obtain vibrational spectra of cationic silicon clusters with 6 to 21 atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] For smaller anionic and cationic clusters, the combination of experiments with high level theory makes it possible to determine the structures of these clusters. [23][24][25] For medium-sized clusters, changes in the structural motif were suggested. Recently, we used infrared multiple photon dissociation (IR-MPD) to obtain vibrational spectra of cationic silicon clusters with 6 to 21 atoms.…”
Section: Introductionmentioning
confidence: 99%
“…2 in Ref. 24). Unlike the quite simple triplet manifold, vibronic interactions are both numerous and complicated in the singlet spectrum, and their study will be addressed in a forthcoming publication.…”
Section: Results and Assignmentmentioning
confidence: 99%
“…10) by Garcia-Fernadez et al confirmed that the major contribution to the X-band is from the 3 A 2 electronic state. 24 In light of the substantial effort to understand the electronic structure of the silicon trimer, it is surprising that no gas-phase excitation spectrum has been reported for either isomer. In this article, we focus on the jet-cooled gas-phase spectrum of Si 3 in the 555-480 nm region, probed by resonant mass-selected two-color two-photon ionization (R2C2PI) and laser-induced fluorescence (LIF)/dispersed fluorescence (DF) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…While C 3 has a singlet linear structure (X 1 Σnormalg+) which is located at 1.91 eV (16930 cm −1 ) below the triplet linear a 3 Π u state, Si 3 is strongly bent with two close‐lying low‐spin 1 A 1 ( C 2v ) and high‐spin 3 normalA2' ( D 3h ) states. Previous extensive quantum chemical computations pointed out that the singlet C 2v structure is the lowest‐lying state of Si 3 , but the corresponding singlet–triplet gap turns out to be small, calculated in the range of 4–15 kJ/mol depending on the methods used …”
Section: Introductionmentioning
confidence: 99%
“…This triatomic species was produced in the 1980s in a number of mass spectrometry experiments using, among others, photofragmentation technique, and laser vaporization followed by a free jet expansion technique . Its electronic structure and spectroscopic parameters were subsequently the subject of several experimental, and theoretical studies . Thermochemical parameters including the total atomization energy (TAE), heat of formation, ionization energy, and electron affinity of Si 3 were also determined …”
Section: Introductionmentioning
confidence: 99%